Microsoft Team-Reading Progress Feature Overcome Foreign Language Speaking Anxiety - Rizky Eka Prasetya (English Education Department, 2024)
The study’s primary goal is to determine whether Microsoft Teams Reading Progress can reduce Foreign Language Speaking Anxiety in the virtual classroom. This study employed a sequential explanatory mixed-methods strategy to gather quantitative data and explain it using qualitative data. The study included 243 International Relations majors in Political Sciences. Results showed that participants’ EFL speaking anxiety decreased significantly after engaging in the Microsoft Teams Reading Progress. The quantitative findings showed that the EFL students need Microsoft Team-Reading Progress Feature to accommodate and assist their English-speaking anxiety. 53.48 % of respondents established that their anxiety decreased while practicing English speaking on the platform. The qualitative result showed that primary Reading Progress features successfully overcame the FLSA. The effect of individual variations may have been balanced by technological aid in the English foreign learners’ Foreign Speaking Anxiety scale. The results indicated that the Artificial Intelligence-generated instructional feedback lowered the FLSA of the participants. Nevertheless, the findings also highlighted the irreplaceable importance of instructors as facilitators and the possibilities of adopting Virtual reality (VR) in teaching foreign language learners, especially speaking competencies